Supply and demand of quranic information in the web environment: a decade of infodemiology study in Iran - Hosseini, Shohreh Seyyed; Alirezaei, Zahra; Basirianjahromi, Reza (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aimed to investigate the demand for information from Iranian users to the supply of scientific products to Iranian researchers in the field of the Quran during the years 2011-2020. The present study is a descriptive-analytical done by web research and scientometric methods using infodemiology indicators. The population included the keywords of Iranian users’ search in the field of the Qur’an - using Google Trends; and in the scientometrics section, the research conducted by Iranian researchers in the area of the Qur’an - indexed in Islamic world citation databases, web of science, and Scopus during the years 2011-2020. A correlation test was performed to investigate the alignment of users ‘information retrieval behavior and researchers’ scientific products using R software. The number of scientific products of researchers and the index of Iranian users’ search volume in the Google search engine has increased over ten years. The average growth of scientific productions of Iranian researchers in the Quranic studies was 411.40. Spearman correlation coefficient between users’ information-seeking behavior and scientific products of Iranian researchers in the field of Quran in the sections of Web search (P-value = 0.001), YouTube search (P-value = 0.0001) and the sum of parts of Google search engine (P-value = 0.0001) was obtained meaningfully. Many factors affect the increasing scientific production of Iranian researchers in the Quranic fields. Information demand or Internet information retrieval behavior of users in this subject can be one of the most critical factors.